2021
DOI: 10.3390/ijerph18115879
|View full text |Cite
|
Sign up to set email alerts
|

Which Risk Factors Matter More for Psychological Distress during the COVID-19 Pandemic? An Application Approach of Gradient Boosting Decision Trees

Abstract: Background: A growing body of scientific literature indicates that risk factors for COVID-19 contribute to a high level of psychological distress. However, there is no consensus on which factors contribute more to predicting psychological health. Objectives: The present study quantifies the importance of related risk factors on the level of psychological distress and further explores the threshold effect of each rick factor on the level of psychological distress. Both subjective and objective measures of risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
0
12
0
1
Order By: Relevance
“…Association among perceived stress, depression, and anxiety were found in a study conducted by [19]. Chen and Liu [20] add up to the previous results when they quantified the importance of related risk factors on the level of psychological distress and explored the threshold effect of each risk factor on the level of psychological distress. They found that health risk factors were the greatest contributors in predicting the level of psychological distress, with a relative importance of 42.32% among all influential factors.…”
Section: Discussionmentioning
confidence: 78%
“…Association among perceived stress, depression, and anxiety were found in a study conducted by [19]. Chen and Liu [20] add up to the previous results when they quantified the importance of related risk factors on the level of psychological distress and explored the threshold effect of each risk factor on the level of psychological distress. They found that health risk factors were the greatest contributors in predicting the level of psychological distress, with a relative importance of 42.32% among all influential factors.…”
Section: Discussionmentioning
confidence: 78%
“…Distance to the nearest greenspace and blue space was the assessment method for seven of these studies. In China, the average distance from a residence to a park was recorded as 37.8 km (Chen & Liu, 2021), while most residents in Mexico reported living within a 10-minute walk of green space (Huerta & Utomo, 2021). A longitudinal study in the UK reported that the majority of residents lived within a 5-min walking distance from the nearest green space (Poortinga et al, 2021).…”
Section: Access To Naturementioning
confidence: 99%
“…The difference perception threshold refers to the minimum difference between two pieces of information that consumers can perceive ( Lalouni et al, 2021 ). Difference sensitivity refers to the minimum sensitivity to differential sensory threshold ( Chen and Liu, 2021 ). Equation (2) is the relationship between sensory intensity and stimulus intensity:…”
Section: Theoretical Basis and Research Hypothesismentioning
confidence: 99%